Factors Affecting Spontaneous Closure of Gastrocutaneous Fistulae After Removal of Gastrostomy Tubes in Children With Intestinal Failure. (September 2015) - Khan, Faraz A.; Fisher, Jeremy G.; Sparks, Eric A.; Iglesias, Julie; Zurakowski, David; Modi, Biren P.; Duggan, Christopher; Jaksic, Tom
Background : Children with intestinal failure (IF) frequently require gastrostomy tubes (GTs) for long-term nutrition support. Risk factors for persistent gastrocutaneous fistulae (GCFs) in pediatric patients with IF are largely unknown but may include underlying nutrition status and duration of indwelling GT. Materials and Methods : Records of patients with IF having undergone GT removal and allowed a trial at spontaneous closure were reviewed. Nonparametric continuous variables were analyzed using the Wilcoxon rank sum test. Post hoc analysis was performed to identify the optimal threshold of GT duration predicting probability of spontaneous closure identified using receiver operating characteristic curve analysis. Results : Fifty-nine children with IF undergoing GT removal were identified. Spontaneous closure occurred in 36 (61%) sites, while 23 (39%) underwent operative closure at a median 67 days after GT removal. The duration of indwelling GT was significantly shorter in the spontaneous closure group (11.5 vs 21 months, P = .002). Of 33 GT indwelling for ≤18 months, 28 (85%) closed spontaneously, compared with only 9 of 26 (35%) with duration >18 months ( P < .001). With GCF persisting beyond 7 days, only 21% (6/28) of sites closed spontaneously, but this dropped to 6% (1/18) of cases with concurrent GT duration >18 months. Conclusions : Of the risk factors evaluated, only prolonged GT duration was associated with an increased likelihood of failure to close spontaneously. It is significantly less likely in pediatric patients with IF in whom GCF persists >7 days, particularly if the duration of GT is >18 months. Relatively earlier operative closure should be considered in this group.